From “I’m not a feminist!” to CASWE President: Reflecting on Space(s), Time(ing), and His(Her)-Story - Wallin, Dawn (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
For this personal narrative, I have used Applebaum and Boyd’s (2000) work on developing a critical sense of dominance to detail my journey of initial resistance to being labeled a feminist, to my growing recognition of power and privilege within educational institutions, to my active role as president of the Canadian Association for the Study of Women in Education (CASWE) for the Canadian Society for the Study of Education (CSSE). I illustrate how working within a system does not negate the potential for a critical engagement with hegemonic practice, but can actually posi- tion feminists, or associations such as CASWE, in spaces to work authentically to- wards equity. Key words: feminism, educational leadership, critical sense of dominance, personal narrative Dans ce récit personnel, l’auteure se sert des travaux d’Applebaum et Boyd (2000) sur le développement d’un sentiment critique de dominance en vue de décrire son cheminement, depuis sa résistance initiale à l’étiquette de « féministe » à son appré‐ ciation grandissante du pouvoir et des privilèges au sein d’établissements d’enseignement et à son rôle actif comme présidente de l’Association canadienne pour l’étude sur les femmes et l’éducation (ACÉFÉ). Elle montre comment le fait de travailler à l’intérieur d’un système n’exclut pas la possibilité d’un engagement criti‐ que vis‐à‐vis d’une pratique hégémonique, mais peut effectivement placer des féministes ou des associations comme l’ACÉFÉ en position favorable pour travailler vraiment à la défense de l’équité. Mots clés : féminisme, leadership en éducation, sentiment critique de dominance, récit personnel.